Ya Anam Ölürse (Öyküler) - Zavotçu, Gencay (Academician Publishing Book DOI Portal, 2023)
Bu kitap, Gencay Zavotçu tarafından yazılan Ÿa Anam Ölürseädlı öykü kitabının tanıtım metnidir. Kitabın amacı, okurlara öyküleri sunmak ve beğeni kazanmaktır. Yazar, yaşamı öykü tadında yaşamayı ve yazıya dökülenleri okurlarla paylaşmayı hedeflemektedir. This book is a promotional text for the short story book Ÿa Anam Ölürseẅritten by Gencay Zavotçu. The aim of the book is to present the stories to the readers and gain their appreciation. The author aims to live life in the form of stories and share them with the readers through writing.